Science Learning Training Using Information Technology in The Covid-19 Pandemic - Muhammad Taufiq; Noer Laelly Baroroh TAG; Estin Nofiyanti; Nandhini Hudha Anggarasari (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The Covid-19 pandemic has a direct impact on the environment of society, both regarding aspects of knowledge and aspects of problem solving which are all trial and error or speculative on various things, as a result in the world of education it is also inseparable from various problems, so that not a few end up leading to conflicts or debate. This community service program (PKM) is aimed at SMA Muhammadiyah Pangandaran teachers with the aim of being able to help solve problems, especially those related to the Teaching and Learning Process in the form of networks (online) in the field of science learning. For this reason, it is necessary to have a technology device that can help teaching and learning activities, especially internet-based information technology applications, with the hope that the online teaching and learning process can take place as it should. and motivate teachers to teach. The results of this PKM activity are in the form of increased motivation or enthusiasm for teaching and additional insight into the use of Information Technology (IT) in carrying out the On Line-based Teaching and Learning Process. In conclusion, the PKM which was appointed under the title Science Learning Training Using Information Technology in the Covid-19 Pandemic Period provided an adequate contribution to 32 SMA Muhammadiyah Pangandaran teachers as training participants.